1988
DOI: 10.1029/jd093id02p01389
|View full text |Cite
|
Sign up to set email alerts
|

Emission of NO and deposition of O3 in a tropical forest system

Abstract: Rates for emission of NO and deposition of O3 were measured at a tropical forest site in Reserve Adolfo Ducke, near Manaus, Brazil. Two independent techniques were used to determine the NO flux: (1) a soil enclosure method and (2) a method based on simultaneous observations of NO and O3 vertical profiles at night, when NO is irreversibly removed by reaction with O3. Results obtained using the two techniques agreed well, giving an average NO flux of 5.2±1.7×1010 molecules cm−2 s−1 and an average vertical exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
3

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(80 citation statements)
references
References 40 publications
3
74
3
Order By: Relevance
“…Underpredicted NO and NO y concentrations in the model might, in turn, be related to underestimated NO emissions from tropical forests. Flux measurements have shown that soils have high emissions of NO x in the forested regions of both central Amazonia (40)(41)(42)(43) and southeast Asia (44). The above-soil NO x emission modeled in the CTM for the wet season of central Amazonia was 10 times lower than the observations reported in the literature (SI Appendix).…”
Section: Discussioncontrasting
confidence: 49%
“…Underpredicted NO and NO y concentrations in the model might, in turn, be related to underestimated NO emissions from tropical forests. Flux measurements have shown that soils have high emissions of NO x in the forested regions of both central Amazonia (40)(41)(42)(43) and southeast Asia (44). The above-soil NO x emission modeled in the CTM for the wet season of central Amazonia was 10 times lower than the observations reported in the literature (SI Appendix).…”
Section: Discussioncontrasting
confidence: 49%
“…219 and Rennenberg 1996). The range of NO 2 compensation points measured for leaves in this study (0.52-1.60 ppbv) is comparable to the value of 1.15 ppbv reported in a past study of wheat leaves and 1.60-1.90 in beech trees (Gessler et al 2000;Kaplan et al 1988), but is somewhat higher than the range reported for coniferous trees (0.1-0.7 ppbv; Rondon et al 1993;Rondon and Granat 1994). NO 2 compensation points were generally related to leaf N concentration with the highest compensation points corresponding to the highest leaf N concentrations (Table 1).…”
Section: Discussionsupporting
confidence: 72%
“…Soil fluxes of NO and within-canopy NO y concentrations have been reported to be higher in the dry season than during the wet season in tropical wet forests (Bakwin et al 1990;Kaplan et al 1988). We therefore investigated if tropical tree leaves take up NO 2 at a higher rate in the dry season compared to the wet season.…”
Section: Discussionmentioning
confidence: 99%
“…Andreae et al (1992) came to a similar result for their early night experiment in the Congo (see Table 1). They estimated the chemical contribution to O 3 deposition as only about 35% by assuming the relatively high NO dry season soil emissions measured by Kaplan et al (1988) in central Amazonia. In both cases, a significant additional sink is necessary to close the early night ozone budget.…”
Section: Ozone Deposition Mechanismsmentioning
confidence: 99%